841 Global child health mentorship. (17th August 2022) - Sousa, Paula de; Searle, Rebecca; Devakumar, Delan
Abstract : Aims: The (ICHG) started a new mentorship scheme for students and professionals with an interest and a passion for global child health. Mentors are paired with mentees around the world aiming to share career advice, opportunities and knowledge with a focus on global child health. Mentors and mentees also have access to a virtual platform where they can share resources, discussions and advice. Starting a career in global child health can be difficult as there is often no clear career pathway. This is one of the first global child health mentorship schemes in the UK. The mentorship scheme is open to anyone with an interest in global child health: medical or non-medical healthcare professional, student, volunteer or in paid employment. Methods: Mentors were invited to fill in an application form and complete e-learning on mentoring. Their profiles were added to an online Mentor Directory on the ICHG website. Mentees also filled out an application form and were able to preference mentors according to their interests and career objectives. The chosen mentor was given a choice as to whether they felt they could meet these objectives and the two were subsequently paired and invited to join the virtual platform. Giving both the mentors and mentees a choice maximises the chances of a suitable match and ongoing engagement in the mentorship scheme. Six months after launching the scheme, anonymous feedback was obtained from mentors and mentees using an online form. Results: The scheme currently has 40 mentees and 50 mentors. 34% (n=17) of mentors and 25% of mentees (n=10) are non-UK based, from 13 different countries. 15% of mentees completed the feedback. Of these, 83.4% had met their mentor, up to three times in six months and the remaining mentees had not met their mentors. Over half (66.7%) had an upcoming meeting planned. On a 5-point Likert scale of how useful they found their meeting (1 not useful to 5 extremely useful), 66.7% scored 4 or 5. Most mentees said they had hoped to get advice on research (66.7%) and careers (50%). The most commonly discussed topic was career (66.7%). Of those surveyed, 83.3% would recommend this mentorship programme. 42% of mentors completed the feedback. Of these, 100% had met their mentee(s) and 37.5% had a future meeting planned. On the Likert scale, 37.5% rated a 4 or 5 for how useful they thought their mentee found the meeting. The main topics discussed were research (100%) and career (87.5%). Of those surveyed, 90.5% of mentors would recommend this mentorship scheme. 81% of Mentors felt they would benefit from formal mentorship training. Conclusion: The ICHG has started a global mentorship scheme with mentors and mentees from 14 different countries. Following the feedback, the ICHG will now focus on empowering mentors with training and will be running a formal Mentorship Training session. We will continue to recruit mentors and mentees from a wide range of backgrounds and enhance the use of the virtual platform, to help create a global child health community.